Extracellular Nicotinamide Phosphoribosyltransferase Is a Component of the Senescence-Associated Secretory Phenotype - Kuehnemann, Chisaka; Hu, Kang-Quan; Butera, Kayla; Patel, Sandip K.; Bons, Joanna; Schilling, Birgit; Aguayo-Mazzucato, Cristina; Wiley, Christopher D. (Frontiers in Endocrinology, 2022)
Cellular senescence is a stress or damage response by which a cell adopts of state of essentially permanent proliferative arrest, coupled to the secretion of a number of biologically active molecules. This senescence-associated secretory phenotype (SASP) underlies many of the degenerative and regenerative aspects of cellular senescence - including promoting wound healing and development, but also driving diabetes and multiple diseases of age. We find that nicotinamide phosphoribosyltransferase (NAMPT), which catalyzes the rate-limiting step in nicotinamide adenine dinucleotide (NAD) biosynthesis, is elevated in senescent cells, but without a commensurate increase in NAD levels. This elevation is distinct from the DNA damage response, in which NAD is lost, and recovery of NAD by NAMPT elevation is AMPK-dependent. Instead, we find that senescent cells release extracellular NAMPT (eNAMPT) as part of the SASP. eNAMPT has been reported to be released as a catalytically active extracellular vesicle-contained dimer that promotes NAD increases in other cells and extends lifespan, and also as free monomer that acts as a damage-associated molecular pattern and promotes conditions such as diabetes and fibrosis. Senescent cells released eNAMPT as dimer, but surprisingly eNAMPT appeared in the free fraction while being depleted from exosomes. Finally, diabetic mice showed elevated levels of eNAMPT, and this was lowered by treatment with the senolytic drug, ABT-263. Together, these data reveal a new SASP factor with implications for NAD metabolism.